Developing new behavior strategies of robot soccer team SjF TUKE Robotics: Category MiroSot. (30th September 2016) - Hajduk, Mikuláš; Sukop, Marek; Jánoš, Rudolf; Semjon, Ján; Tuleja, Peter; Rusnak, Rudolf; Špak, Michal
There are too many types of robotic soccer approaches at present. SjF TUKE Robotics, who won robot soccer world tournament for year 2010 in category MiroSot, is a team with multiagent system approach. They have one main agent (master) and five agent players, represented by robots. There is a point of view, in the article, for code programmer how to create new behavior strategies by creating a new code for master. There is a methodology how to prepare and create it following some rules.